Pengembangan Aplikasi E-Learning Akuntansi Sektor Publik dengan Metode Prototyping - maryadi maryadi; Miftahul Hadi; syanni yustiani (Universitas Riau Kepulauan, 2022)
The development of computer-based learning models (e-learning) is so rapid. In Indonesia, various universities have implemented e-learning for their students. In addition, in- general, there are many e-learning applications that offer learning packages that can be used by learners. However, the learning packages offered to the general public are still limited (some are paid). With the enthusiasm to succeed the independent learning policy launched by the government, the researcher proposes an e-learning application that presents material on public sector accounting. This public sector accounting e-learning application can be used for free by anyone, anytime, anywhere with any teacher.Given that users of public sector accounting e-learning are all levels of Indonesian society whose needs are difficult to identify, there will be a big challenge in developing e-learning that suits user needs. Therefore, the development of public sector accounting e-learning is proposed using the prototyping method. The system development steps consist of planning, analysis, design and implementation stages. In the analysis stage, the researcher develops an initial prototype and analyzes user needs by submitting a survey to get the level of user wawsatisfaction as measured by the Customer Satisfaction Index method and explores user needs.This study shows that the curriculum-based prototype of e-learning Public Sector Accounting provides a level of user satisfaction (Customer Satisfaction Index) which can be categorized into excellent criteria, which is 90.52%. In addition, based on a survey on the initial prototype, many students want learning media in the form of slides, videos and practice questions.